Phenocopy or variant: a longitudinal study of very slowly progressive frontotemporal dementia. (7th February 2013) - Brodtmann, Amy; Cowie, Tiffany; McLean, Catriona; Darby, David
Abstract : Frontal variant frontotemporal dementia (fvFTD) can present with a range of social and cognitive impairments. Complicating this clinical picture is a group of non-progressive or 'phenocopy' patients. We present a patient and his father with very slowly progressive fvFTD over decades. Stable MRI and positron emission tomography (PET) imaging abnormalities were present in the presenting patient, with serial neuropsychological assessments that showed no significant change over 15 years. His father also had a 20-year history of functional decline, associated with neuropsychological evidence of change. Neuropathological confirmation of the condition of his father became available. This revealed gross bilateral frontal atrophy and spongiosis in the frontal cortical regions with mild neuronal loss and rounded ubiquitinated perinuclear inclusions, consistent with early stage frontotemporal lobar degeneration with ubiquitin by current neuropathological criteria. The phenotype of frontal variant FTD is broad. Many patients present with frontal networks dysfunction. We present evidence that some patients with a very slow clinical progression do have FTD.